SIFAT AIR LINDIAN DAN TANAH SERTA RESPON TANAMAN PADA MODIFIKASI TEKSTUR, TEHNIK PENGAIRAN DAN APLIKASI LIMBAH PERIKANAN PADA TANAH LAHAN BASAH GARAMAN DARI DESA PANTAI HARAPAN TANAH LAUT KALIMANTAN SELATAN UNTUK PRODUKSI BAWANG MERAH DAN SAWI SISTEM POT - Fachruzi, Ismed; Tony, Frans (EnviroScienteae, 2023)
The nature of the soil is massive and saline, not fertile for horticultural crops such as shallots and mustard greens. The soil properties of Tidal Wetland Type-A (direct), the soil sample mentioned above, is known from the analysis results to have an EC value of 153.5 ds/m (very high), Na (1 NH4Oac) 1.21 me/ 100 g soil (very high), pH (1: 5 H2O) 6.74 (neutral), C-organic (Walkley-Black) 2.08% (medium), clay soil texture (clay 76%) and massive structure, Such land is very difficult for agricultural plants such as horticulture to grow, because it is difficult for the soil to pass water and salt which poisons plants. The application of sand, irrigation methods, and organic materials can change the properties of the soil and support the growth of shallots and mustard greens.